Public funding of health at the district level in Indonesia after decentralization - sources, flows and contradictions - Harahap Nida P; Heywood Peter (BMC, 2009)
Abstract Background During the Suharto era public funding of health in Indonesia was low and the health services were tightly controlled by the central government; district health staff had practically no discretion over expenditure. Following the downfall of President Suharto there was a radical political, administrative and fiscal decentralization with delivery of services becoming the responsibility of district governments. In addition, public funding for health services more than doubled between 2001 and 2006. It was widely expected that services would improve as district governments now had both more adequate funds and the responsibility for services. To date there has been little improvement in services. Understanding why services have not improved requires careful study of what is happening at the district level. Methods We collected information on public expenditure on health services for the fiscal year 2006 in 15 districts in Java, Indonesia from the district health offices and district hospitals. Data obtained in the districts were collected by three teams, one for each province. Information on district government revenues were obtained from district public expenditure databases maintained by the World Bank using data from the Ministry of Finance. Results The public expenditure information collected in 15 districts as part of this study indicates district governments are reliant on the central government for as much as 90% of their revenue; that approximately half public expenditure on health is at the district level; that at least 40% of district level public expenditure on health is for personnel, almost all of them permanent civil servants; and that districts may have discretion over less than one-third of district public expenditure on health; the extent of discretion over spending is much higher in district hospitals than in the district health office and health centers. There is considerable variation between districts. Conclusion In contrast to the promise of decentralization there has been little increase in the potential for discretion at the district level in managing public funds for health - this is likely to be an important reason for the lack of improvement in publicly funded health services. Key decisions about money are still made by the central government, and no one is held accountable for the performance of the sector - the district blames the center and the central ministries (and their ministers) are not accountable to district populations.